Impact of the oil sector on the financial security of the national economy (Journal of Economic Research & Business Administration, 2020)
This study examines aspects of the impact of the raw material orientation of the economy on maintainingits financial security in the short and long term. Relevance of this topic is given by crisis phenomenain the world and national economies, generated, first of all, by negative price conditions in theworld raw materials market. It is precisely in the conditions of the crisis that all the problems existing inthe state are most clearly manifested, the shortcomings of the system for ensuring the most importantarea of national security – financial, are revealed. During such periods, authorities should attach particularimportance to the security issues of the state, organizations and citizens, develop effective toolsto eliminate emerging threats or mitigate their consequences. The current state of the National Fund ofthe Republic of Kazakhstan activity has been analyzed in detail, since the dynamics of changes in thevolumes of assets and the level of the fund’s profitability reflect how effectively the government’s work isorganized in generation and using the state’s raw materials income, that ensures financial security for thecountry with a raw material focus. It is concluded that the solution to the problem of financial securityof the Republic of Kazakhstan can be achieved only by consistently pursuing a policy to diversify theeconomy, which will lead to a reorientation of income derived from commodity exports.